Veiled Threats Representing the Muslim Woman in Public Policy Discourses - Rashid, Naaz (Policy Press, 2008)
As Muslim women continue to be a focus of media-led debate, Naaz Rashid uses original scholarship and empirical research to examine how Muslim women are represented in policy discourse and how the trope of the Muslim woman is situated within national debates about Britishness, the death of multiculturalism and global concerns over international terrorism.